How individuals with the irritable bowel syndrome describe their own symptoms before formal diagnosis. (2nd October 2015) - Molinder, Herdis; Agréus, Lars; Kjellström, Lars; Walter, Susanna; Talley, Nicholas J.; Andreasson, Anna; Nyhlin, Henry
Abstract: Aim : To investigate how individuals fulfilling the Rome II criteria for irritable bowel syndrome (IBS) spontaneously described their symptoms. Method : From a general population, 1, 244 randomly sampled adults were asked to describe their gastrointestinal symptoms (if any) verbally, in their own words, at a semi-structured interview. Their own descriptions were sorted into five symptom clusters. The participants independently completed a written questionnaire (the Rome II Modular Questionnaire (RMIIMQ)). Results : A total of 601 participants reported at least one gastrointestinal symptom, and 128 had IBS according to the RMIIMQ. After exclusion of organic causes, previously diagnosed IBS, or additional gastrointestinal diagnosis, 81 participants with IBS according to RMIIMQ remained. Five participants (6%) described symptoms included in the full definition of IBS, but none fulfilled the Rome II criteria completely. Abdominal pain or other IBS-related symptoms were reported by 64 (79%), and 12 (15%) did not report any IBS-like symptom. Conclusion : Previously undiagnosed individuals, who fulfil criteria for Rome II-IBS, often express their complaints in words that do not fit into the current diagnostic criteria.